Interindividual differences in behavioural and psychophysiological reactions to comfort provided by parent versus strangers in children with severe or profound intellectual disabilities: An attachment perspective. - Sien Vandesande; Carlo Schuengel; Paula Sterkenburg; Guy Bosmans; Bea Maes (OSF Registries, 2020)
In this project, interindividual differences in the extent to which young children with a severe or profound intellectual disability differentiate between their parent as primary caregiver and a stranger, are explored. The outcomes used were behavioural expression of emotion (arousal and valence) and skin conductance during a home-based experimental paradigm. During this experiment, children were confronted with stressors and comfort, randomly provided by their parent or a stranger. This issue is discussed from an attachment perspective.